Lend me your verbs: Verb borrowing between Jingulu and Mudburra. Issue 3 (2nd July 2020) - Meakins, Felicity; Pensalfini, Rob; Zipf, Caitlin; Hamilton-Hollaway, Amanda
ABSTRACT: We discuss two unrelated languages, Jingulu (Mirndi, non-Pama-Nyungan) and Mudburra (Ngumpin-Yapa, Pama-Nyungan), which have been in contact for 200–500 years. The language contact situation is unusual cross-linguistically due to the high number of shared nouns, tending to an almost shared noun lexicon. Even more unusually, this lexicon was formed by borrowing in both directions at a relatively equal rate. The aim of this paper is to extend the bidirectional noun borrowing results to the verbal systems of Jingulu and Mudburra to determine whether a similarly high rate of borrowing occurred, and if so, whether it was similarly bidirectional. The high degree of shared Jingulu–Mudburra verb forms was first observed by Pensalfini who claimed that Jingulu and Mudburra lexical verbs are almost entirely cognate across these two languages. This paper aims to quantify the degree of shared verb forms and determine the direction of borrowing between Mudburra and Jingulu. We first establish shared forms and then determine the origins of the forms based on a comparative database of verbs from geographic and phylogenetic neighbours (Wambaya, Gurindji and Jaminjung).